Decoupling Electron‐ and Phase‐Transfer Processes to Enhance Electrochemical Nitrate‐to‐Ammonia Conversion by Blending Hydrophobic PTFE Nanoparticles within the Electrocatalyst Layer (Adv. Energy Mater. 9/2023). Issue 9 (3rd March 2023) - Gao, Jianan; Ma, Qingquan; Young, Joshua; Crittenden, John C.; Zhang, Wen
Abstract : Nitrate‐to‐Ammonia Conversion In article number 2203891, Wen Zhang and co‐workers report the blending of a proper level (surface area ratio, PTFE:CuO = 2.5) of hydrophobic polytetrafluoroethylene nanoparticles into a CuO electrocatalyst layer. This is shown to enhance the spillover and transport of gaseous products (e.g., ammonia) from the electrocatalyst surface and enhance the nitrate‐to‐ammonia yield by over 17 fold in electrochemical membrane stripping.